Quality of Life in Individuals with Primary Headache Disorders: A Cross-Sectional Analysis at Tribhuvan University Teaching Hospital - Rajbhandari, Reema; Shahi, Tejash; Khanal, Ujjwal Prakash; Karna, Ragesh; Ojha, Rajeev; Gajurel, Bikram Prasad (Nepal Journal of Neuroscience, 2024)
Introduction: Headache disorders are among the most common health conditions worldwide, with a significant global burden, particularly from primary headaches such as migraine and tension-type headache (TTH). In Nepal, the prevalence of headache disorders is high, with a considerable portion of the population affected by these conditions. Primary headache disorders have been shown to negatively impact the quality of life (QoL) of individuals, both physically and mentally.Objective: This study aimed to assess the quality of life in patients diagnosed with primary headache disorders, including migraine, TTH, and other related conditions, at the Tribhuvan University Teaching Hospital in Nepal.Materials and methods: An observational descriptive cross-sectional study design was used, with a sample size of 211 patients diagnosed with primary headache disorders. Participants were selected using a non-probability convenience sampling method. A structured questionnaire was administered to collect demographic, clinical, and QoL-related data. The Quality of Life was measured using the Short Form (SF-36) questionnaire, which provides two key summary measures: the Physical Component Summary (PCS) and Mental Component Summary (MCS). Data was analyzed using SPSS Version 29, employing descriptive statistics, independent t-tests, ANOVA, and multiple linear regression to identify associations and predictors of QoL.Results: Preliminary results indicate that primary headache disorders significantly impair both the physical and mental health of affected individuals, as evidenced by lower PCS and MCS scores. Factors such as age, duration of illness, type of headache disorder, and medication use were identified as key determinants influencing the quality of life in these patients.Conclusion: The findings of this study highlight the substantial impact of primary headache disorders on the quality of life of individuals. Understanding the factors that contribute to the reduced QoL in these patients is crucial for developing effective interventions and improving the management of primary headache disorders in Nepal.